COVID-19 Conceptual Metaphors in Indonesian Newspapers - Nursanti, Emi; Andriyanti, Erna; Wijaya, Ikha Adhi (Universitas Sanata Dharma, 2024)
Conceptual metaphor plays a significant role in everyday communication as it is a fundamental aspect of the human mind and conceptualization. It reflects people’s ways of thinking in responding to a phenomenon or event. To describe how online media in Indonesian report the COVID-19 pandemic metaphorically, the study would explain 1) the mapping of conceptual metaphors related to COVID-19, and 2) their cognitive functions or ways of thinking about COVID-19. This qualitative study analyzed metaphorical lexical units in three online newspapers in Bahasa Indonesia with local and national coverage: Kompas, Jawa Pos, and Kedaulatan Rakyat. The Metaphor Identification Procedure (MIP) was used in the data collection process and Conceptual Metaphor Theory (CMT) was used to analyze the data. The study found that Indonesians are rich in lexical items as source domains to conceptualize things related to the COVID-19 pandemic. The prominent source domains, inter alia, are WARFARE, DESTRUCTIVE FORCE, COLOR SPECTRUM, and MOVEMENT. The conceptual metaphors illustrate how people feel, act, and think about COVID-19. The dominance of lexical items in WARFAFE and DESTRUCTIVE FORCE categories implies that the metaphors were used to raise people’s awareness that they were in a difficult situation and needed to fight the virus together.